EVALUASI PEMBELAJARAN PADA KONDISI EXTRAORDINARY: PERSPEKTIF MAHASISWA AKUNTANSI - Hempry Putuhena (Department of Accounting, Faculty of Economics and Business, Universitas Tadulako, 2023)
The extraordinary event that is currently happening is the COVID-19 pandemic. The existence of the COVID-19 pandemic has an impact on all levels. One that has a significant impact is the learning method. Online learning does not necessarily run well, some universities face various kinds of obstacles. This study aims to find out how extraordinary conditions that are currently occurring, such as the Covid-19 pandemic, have an impact on the lecture process for accounting students. This study uses surveys and research data obtained by using questionnaires filled out online by students using GoogleForm. 242 accounting students who responded to the survey conducted. The result of this study indicate that the teaching and learning aspect needs to be a full concern for the department because it is still constrained by the internet network, the lecturer capability aspect during online lectures is still of high quality, and the infrastructure aspect is an aspect that needs to be considered by the department because not all students have the same economic background. So that these three aspects need to be considered by the department so that online lectures can run well.